2018
DOI: 10.1038/bjc.2018.9
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 mRNA expression in plasma-derived exosomes is associated with response to anti-PD-1 antibodies in melanoma and NSCLC

Abstract: This corrects the article DOI: 10.1038/bjc.2017.85.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(175 citation statements)
references
References 14 publications
7
165
1
2
Order By: Relevance
“…For example, 12.Nabet et al [14] reported that an unshielded exosome (RNA RN7SL1) acts as a damage-associated molecular pattern (DAMP) to activate the pattern recognition receptor, RIG-I, to drive anti-viral signaling when transferred to recipient breast cancer cells via an exosome that ultimately leads to tumor growth and therapy resistance. The CD274 mRNA in plasmaderived EVs is related to the response to anti-PD-1 antibodies in melanoma and non-small cell lung cancer [15]. These results reveal the potential of exLRs to be applied in the diagnosis of human cancers and cell-to-cell mediators of metastasis.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, 12.Nabet et al [14] reported that an unshielded exosome (RNA RN7SL1) acts as a damage-associated molecular pattern (DAMP) to activate the pattern recognition receptor, RIG-I, to drive anti-viral signaling when transferred to recipient breast cancer cells via an exosome that ultimately leads to tumor growth and therapy resistance. The CD274 mRNA in plasmaderived EVs is related to the response to anti-PD-1 antibodies in melanoma and non-small cell lung cancer [15]. These results reveal the potential of exLRs to be applied in the diagnosis of human cancers and cell-to-cell mediators of metastasis.…”
Section: Introductionmentioning
confidence: 78%
“…It has been shown that EV long RNAs (exLRs), including circular RNA (circRNA), long non-coding RNA (lncRNA), and messenger RNA(mRNA), are in human plasma EVs and play a vital role in the progression of tumor development [12][13][14][15]. For example, 12.Nabet et al [14] reported that an unshielded exosome (RNA RN7SL1) acts as a damage-associated molecular pattern (DAMP) to activate the pattern recognition receptor, RIG-I, to drive anti-viral signaling when transferred to recipient breast cancer cells via an exosome that ultimately leads to tumor growth and therapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The FDA has approved PD-L1 immunohistochemistry as a companion diagnostic indicator for anti-PD-1 therapy in patients with non-small cell lung cancer (NSCLC) (24)(25)(26). Programmed death 1 ligand on the tumorderived exosomes released from some types of tumor is involved in the immune evasion of tumor cells (27)(28)(29). In the preclinical model of colorectal cancer, administration of PD-L1 antibody in combination with the inhibition of exosomal PD-L1 secretion could achieve tumor-suppressive effects (28).…”
Section: Pd-1 Ligand Expressionmentioning
confidence: 99%
“…Melanoma patients responding to pembrolizumab could be distinguished from non-responders by increased levels of EV PD-L1 at 3 to 6 weeks after the start of therapy [97]. In another study, it was shown that exosomal PD-L1 mRNA levels decreased during nivolumab or pembrolizumab treatment of melanoma patients with complete or partial response, while in patients with progressive disease EV PD-L1 expression was increased [98].…”
Section: Predicting the Response To The Ici Therapymentioning
confidence: 99%